CGIAR Research Program on Rice - Plan of Work and Budget 2020 - CGIAR Research Program on Rice (CGIAR Research Program on Rice, 2020)
There are no major modifications to the overall of theory of change, except for FP5 (new rice varieties) which will emphasize the modernization of its breeding programs in order to accelerate the development and delivery of improved varieties to our partners and farmers. To test the validity of our overall theory of change, we will emphasize in the last two years of RICE the collection, analysis, and reporting of adoption and impact of RICE technologies, tools, policies, etc. Complementary to studying successes of adoption, IRRI will lead an analysis of under-reported so-called 'failures' around scaling and mechanisms to constructively learn from them so that RICE, and the CGIAR in general, is more cognizant of the complexities of impact pathways and the role that the CGIAR is best placed to play as one moves from the sphere of control to the spheres of influence and interest.